Painting the Visible World : Painters at the Euston Road School and at Camberwell School of Arts & Crafts 1930-1960. (London : Austin/Desmond Fine Art, 1989)
Bell, Graham ; Buhler, Robert ; Carter B A R ; Coldstream, William ; Daniels, Leonard ; Darwin, Robin ; Dawnay, Denis ; Eyton, Anthony ; Feild, Maurice ; Frost, Terry ; Gowing, Lawrence ; etc.
Painting the Visible World : Painters at the Euston Road School and at Camberwell School of Arts & Crafts 1930-1960, Austin/Desmond Fine Art, London, 1989
boek